Fermentation and drying effects on bread-making potential of sour cassava and ahipa starches. (February 2019) - Díaz, Andrea; Dini, Cecilia; Viña, Sonia Z.; García, María Alejandra
Abstract: Cassava sour starch is a gluten-free product obtained by natural fermentation and sun-drying that outstrips the native starch baking expansion properties. Although maize starch has been subjected to a similar process, this desirable feature could not be achieved. Ahipa, an unexploited tuberous root, renders starch with relatively low gelatinization temperature and amylose content, like that of cassava. The aim of this work was to study the characteristics and technological properties of ahipa starch subjected to different fermentation processes and drying methods (oven- or sun-drying) and compare the bakery quality of its derived products to those from fermented cassava starches. Ahipa starch followed similar fermentation paths to those followed by cassava's, and sun-drying significantly reduced the content of the resultant lactic and butyric acids. Rheological behavior of starch pastes as well as moisture content and hardness of the doughs obtained from fermented and sun-dried ahipa starches differed from those of cassava. Sun-light exposure resulted detrimental for the expansion properties of ahipa sour starches, while the native one showed baking expansion properties like those of fermented sun-dried cassava starch. Thus, ahipa starch represents an interesting ingredient for the elaboration of gluten-free baked products. Graphical abstract: Unlabelled Image Highlights: Ahipa and cassava starches behaved differently under fermentation and sun-drying. Fermentation did not improve the baking expansion of ahipa starch. Sun-drying was ineffective or even diminished fermented ahipa starch baking expansion. Ahipa native starch showed similar baking expansion to fermented cassava starch. Dough hardness and moisture correlated to the baking expansion of cassava starches.